Digestible energy as a criterion for the development of diets for the African sharptooth catfish, Clarias gariepinus (Pisces: Clariidae) - Rouhani, Q A (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1993)
Based on a number of attributes, the African sharptooth catfish, Clarias gariepinus is an ideal aquaculture species. Much work has been undertaken on developing the technology for the commercial culture of the species inclusive of determining the nutritional requirements for cost effective feed formulation. However, digestible energy (DE) values for specific feed ingredients were unknown. As DE values are not interchangeable between species, this study set out to determine the DE values for conventional and unconventional feed-ingredients for the formulation of an optimal feed. The ultimate goal in feed formulation is to produce a diet that supports the maximum production at the least cost. The indirect method was found to be most suitable in obtaining DE values for the catfish. Feed samples were marked by adding 2% chromic oxide as an inert indicator. The fish were then force-fed and faecal samples were obtained from the hindgut by stripping the fish 10 hours after feeding as this was found to be when the hind-gut was at its fullest and the feed maximally digested. A linear based computer programme was used to formulate experimental diets using the established DE values as an additional variable. The formulated feed was tested and compared to a commercial catfish diet and a standard reference diet (H-440). All of the newly formulated feeds were found to be cheaper to manufacture (by between 5 and 10%). Statistically (ANOVA), all of the experimental diets resulted in higher specific growth rates (SGR) than the standard reference diet. The commercial diet also resulted in a lower SGR than those experimental diets with similar protein levels.
Keywords: Clariidae; Catfishes -- Africa; Catfishes -- Nutrition -- Requirements -- Africa; Catfishes; Clarias